Composite high-temperature-resistant material containing glass fiber yarns and preparation method thereof

By optimizing the preparation process and ingredients of glass fiber cloth and using modified sizing agents and phenolic resin modified glue, the problems of insufficient oxidation resistance, high temperature resistance and wear resistance of glass fiber composite materials in the existing technology have been solved, and achieved Higher material performance.

CN119332508AActive Publication Date: 2025-01-21ZIBO ANDUN NEW MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411885766.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The prior art has not been modified by glass fiber wetting agents and phenolic resin components, resulting in insufficient oxidation resistance, high temperature resistance and wear resistance of glass fiber composite materials.

Method used

Modified sizing agent and phenolic resin modified glue are used, and the preparation process and ingredients of the glass fiber cloth are optimized. Phenylsuccinic anhydride modified starch is used in the modified sizing agent, and urotropine is added to the phenolic resin modified glue. Curing agent and flame retardant and antioxidant filler.

Benefits of technology

It significantly improves the antioxidant, high temperature and abrasion resistance of glass fiber composite materials, avoids the phenomenon of random gauze winding in the textile process, and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of composite high-temperature-resistant materials, and particularly relates to a composite high-temperature-resistant material containing glass fiber yarns and a preparation method thereof. According to the modified impregnating compound disclosed by the invention, a modified film-forming agent prepared from phenyl succinic anhydride modified starch has excellent adsorption film-forming property; phenolic resin modified glue is obtained by modifying 4-vinyl-2, 6-dimethoxy-phenol through 1, 1, 3, 5, 5-pentamethyl-3-phenyltrisiloxane, then compounding the modified 4-vinyl-2, 6-dimethoxy-phenol with phenol and reacting with formaldehyde, the thermal stability of phenolic resin can be enhanced, aminated boron nitride obtained by ball-milling boron nitride and urea has the advantages that the thermal stability of the phenolic resin is improved, and the thermal stability of the phenolic resin is improved. And the flame-retardant antioxidant filler obtained by compounding with the aluminum oxide ceramic powder and the carbon black powder enhances the interface bonding force with the phenolic resin modified glue. After the glass fiber yarns are woven into the glass fiber cloth, the flame-retardant antioxidant filler is bonded by infiltrating the phenolic resin modified glue, and the prepared composite high-temperature-resistant material containing the glass fiber yarns has excellent antioxidant, high-temperature-resistant and wear-resistant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite high temperature resistant materials, and in particular relates to a composite high temperature resistant material comprising glass fiber yarn and a preparation method thereof. Background Art

[0002] Glass fiber materials have the characteristics of high mechanical strength, low elongation, corrosion resistance, and good impact resistance, so they are widely used in the fields of construction, aerospace, and electronic appliances. Although glass fiber materials have high tensile strength, they have large dynamic friction coefficients and bending stiffness, so they are prone to hairiness and yarn entanglement during the weaving process.

[0003] The Chinese invention patent with publication number CN110863360B discloses a preparation process of electronic-grade glass fiber cloth that is resistant to high temperature and corrosion. The ordinary alkali-free fiber cloth is dipped in a glue solution of 5-35% polysiloxane emulsion, 0.5-5% surfactant, 3-20% ethanoic acid alcohol solution, 1-5% silane coupling agent, and the balance is water. After acid treatment, the cloth is dipped in a glue solution of 8-15% epoxy resin, 1-5% xanthan gum, 0.5-2.5% EDTA, 0.1-1% propylene glycol, 3-8% trimethylolpropane triacrylate, 0.1-0.5% stabilizer, 0.1-0.5% antistatic agent, 1-12% silane coupling agent, and the balance is water. Finally, the surface is treated to obtain a weight per unit area of ​​100-200g / m 2 Electronic grade glass fiber cloth. The Chinese invention patent with publication number CN117484407A discloses an environmentally friendly grinding wheel mesh, which is composed of glass fiber mesh and environmentally friendly phenolic resin glue. The environmentally friendly phenolic resin glue is composed of the following formula in mass percentage: 30-35% thermosetting phenolic resin, 4-6% emulsifier, 0.4-0.6% thickener, 0.1-0.3% coupling agent, 4-6% solvent, 55-60% water. However, the prior art has the technical problem of not modifying the glass fiber impregnation agent and phenolic resin components to improve the anti-oxidation, high temperature resistance and wear resistance of the glass fiber composite material. Summary of the invention

[0004] The object of the present invention is to provide a composite high-temperature resistant material comprising glass fiber yarn and a preparation method thereof, so as to solve the technical problem in the prior art that the glass fiber sizing agent and phenolic resin components are not modified to improve the oxidation resistance, high temperature resistance and wear resistance of the glass fiber composite material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The composite high temperature resistant material containing glass fiber yarn comprises the following raw materials in parts by mass: 80-100 parts of glass fiber cloth, 20-30 parts of modified impregnation agent, 20-30 parts of phenolic resin modified glue, 1-3 parts of urotropine curing agent and 5-6 parts of flame retardant antioxidant filler; The glass fiber cloth is made of glass fiber yarn through plain weaving or twisting weaving. The glass fiber yarn includes the following raw materials by mass: 64-66 parts of silicon dioxide, 15-18 parts of aluminum oxide, 5-6 parts of boron oxide, 5-8 parts of magnesium oxide and 5-8 parts of calcium carbonate; The modified impregnating agent comprises the following raw materials by weight: 20-25 parts of modified film-forming agent, 0.5-1 parts of antibacterial agent, 0.5-1 parts of antistatic agent, 0.5-1 parts of defoaming agent and 7-10 parts of lubricating solvent; The antibacterial agent is one or more combinations of dibutyltin maleate, tributyltin oxide, and dioctyltin dilaurate; the antistatic agent is one or more combinations of alkyl dicarboxymethyl ammonium ethyl lactone, stearyl trimethyl quaternary ammonium salt, and antistatic agent 1631; the defoaming agent is one or more combinations of DF-696, DF-420, and AC-10.

[0006] A method for preparing a composite high temperature resistant material containing glass fiber yarn comprises the following steps: S1. Put silicon dioxide, aluminum oxide, boric acid, magnesium oxide and calcium carbonate into a mixer and stir for 30-50 minutes to obtain a glass mixture. Preheat the crucible to 1200-1300°C, add the glass mixture several times, with an interval of 20-40 minutes between additions. After the additions are completed, heat the mixture to 1500-1600°C and keep it warm for 4-8 hours. After the bubbles are discharged from the molten glass solution, the glass solution is made to flow out in the form of filaments through a porous plate. The filamentary glass fibers are coated with a modified impregnation agent through an oiling roller, and the fiberglass is drawn by a collecting wheel to obtain glass fiber filaments. S2, passing the glass fiber filaments through a warping machine to remove impurities and wind the fiberglass yarns to make glass fiber yarns, and using the glass fiber yarns as warp yarns and weft yarns to weave glass fiber cloth through a loom; S3, adding urotropine curing agent to the phenolic resin modified glue to soak the glass fiber cloth, bonding the flame retardant and antioxidant filler on both sides of the glass cloth, and curing to obtain a crude composite flame retardant and antioxidant filler; S4. Cutting the crude composite flame retardant and antioxidant filler into required specifications to obtain a composite high temperature resistant material product containing glass fiber yarn.

[0007] Preferably, the mass ratio of silicon dioxide to aluminum oxide in the S1 is 3.8-4:1, and the mass ratio of magnesium oxide to calcium carbonate is 0.9-1:1.

[0008] Preferably, the drawing rate of the wire drawing wheel in S1 is 40-50 m / min, and the average diameter of the glass fiber filaments is 5-15 μm.

[0009] Preferably, the single yarn density of the warp yarn and the weft yarn in S2 is 27~30tex.

[0010] Preferably, the mesh number of the glass fiber cloth in S2 is 6-7 and the weight is 200-220 g / m 2 .

[0011] Preferably, the curing in S3 is carried out at 150-170° C. for 1-2 hours.

[0012] Preferably, the method for preparing the modified wetting agent in S1 comprises the following steps: S11. Add 15-20 parts of castor oil and 4.1-5.8 parts of methanol to a reactor by weight, heat to 60-70°C under stirring, add 0.2-0.5 parts of an alkali catalyst, react for 1-2 hours, add 5wt% of dilute sulfuric acid until the pH of the reaction system is 2-3, let stand for 20-24 hours to separate the layers, take the upper layer of liquid, wash with water until neutral, remove impurities by low-pressure fractionation to obtain castor oil methyl ester, blend 15-20 parts of castor oil methyl ester and 1.5-3 parts of dibutyl ester to obtain a lubricating solvent; S12, according to mass parts, add 10-20 parts of starch with a linear content of 55-60% to 80-100 parts of deionized water, stir evenly at a low speed, then drop 6-12 parts of phenylsuccinic anhydride acetone solution, and adjust the pH to 8.4-8.6 with 10wt% sodium hydroxide solution, and drip it within 2-3 hours, react at 30-35°C for 2-3 hours, then drop 5wt% of dilute sulfuric acid to a pH of 6.5-7, filter and wash with deionized water and anhydrous ethanol in turn, dry at 30-40°C, and pulverize and sieve to obtain a modified film-forming agent; S13. Add 20-25 parts of modified film-forming agent, 0.5-1 parts of defoaming agent, 0.3-0.5 parts of antibacterial agent and 0.5-1 parts of antistatic agent to 7-10 parts of lubricating solvent in parts by mass, raise the temperature to 85-95°C under stirring and gelatinize for 1-2 hours to obtain a modified impregnating agent.

[0013] Preferably, the mass ratio of castor oil to methanol in S11 is 10:2.7-2.9.

[0014] Preferably, the base catalyst in S11 is one or more combinations of dimethylamine, 4-dimethylaminopyridine and tetramethylammonium hydroxide.

[0015] Preferably, the method for preparing the phenolic resin modified adhesive in S3 comprises the following steps: S21, according to the mass parts, add 10-15 parts of 4-vinyl-2,6-dimethoxy-phenol into the reaction kettle, heat it to 50-55°C, dropwise add 0.5-2 parts of catalyst and 8-14 parts of 1,1,3,5,5-pentamethyl-3-phenyltrisiloxane, heat it to 80-90°C and react for 2-3h to obtain silane-modified 4-vinyl-2,6-dimethoxy-phenol; S22, according to the mass parts, add 100-115 parts of phenol and 10-15 parts of silane-modified 4-vinyl-2,6-dimethoxy-phenol into the reaction kettle, heat it to 50-55° C., add 0.5-2 parts of metal salt catalyst and 60-70 parts of 37wt% formaldehyde solution after the phenol is completely melted, react at 100-110° C. for 4-8h, and obtain a crude phenolic resin; S23, washing the crude phenolic resin with deionized water, distilling under reduced pressure, adding 50-80 parts of ethanol to dilute to obtain a phenolic resin modified glue.

[0016] Preferably, the synthesis route of the silane-modified 4-vinyl-2,6-dimethoxy-phenol is as follows:

[0017] The results of mass spectrometry analysis were: m / z: 630.25 (100.0%), 631.25 (49.1%), 632.25 (17.6%), 632.26 (5.8%), 633.25 (5.0%), 633.26 (2.1%), 634.25 (1.1%).

[0018] Preferably, the catalyst in S21 is one or more combinations of platinum chloroacid, cyclooctadiene nickel, and Custer platinum catalyst.

[0019] Preferably, the metal salt catalyst in S22 is one or more combinations of zinc acetate, magnesium tartrate and tin oxalate.

[0020] Preferably, the method for preparing the flame retardant and antioxidant filler in S3 comprises the following steps: S31, according to the mass parts, 5-6 parts of boron nitride, 100-150 parts of urea and 50-70 parts of deionized water were mixed evenly, added to a ball mill, and ball milled for 12-16 hours, then added to 200 parts of deionized water, ultrasonicated for 15-30 minutes, and filtered to collect the solid to obtain aminated boron nitride; S32. According to the mass parts, 4-5 parts of amino boron nitride, 5-6 parts of alumina ceramic powder and 20-30 parts of carbon black powder are uniformly mixed to obtain a flame retardant and antioxidant filler.

[0021] Preferably, the average particle size of the alumina ceramic powder in S32 is 1-3 μm, and the average particle size of the carbon black powder is 10-30 μm.

[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. Based on the prior art, the present invention optimizes the preparation process and components of glass fiber cloth. The modified film-forming agent prepared by modifying starch with phenyl succinic anhydride in the modified sizing agent has excellent adsorption film-forming properties, avoiding the phenomenon of disordered yarn entanglement when the glass fiber yarn is woven into glass fiber cloth. The flame-retardant and antioxidant filler is bonded by impregnating the phenolic resin modified adhesive. The obtained product is a composite high-temperature resistant material containing glass fiber yarn, which has excellent antioxidant, high-temperature and wear resistance.

[0023] 2. The present invention uses castor oil methyl ester and dibutyl ester obtained by reacting castor oil with methanol to blend the lubricating solvent, which has good lubricating and plasticizing properties; the modified film-forming agent is obtained by modifying starch by adding phenylsuccinic anhydride acetone solution, and the hydroxyl groups in the starch undergo esterification reaction with phenylsuccinic anhydride, and phenyl hydrophobic groups are grafted on the side chains, so that the high-temperature stability of the starch is improved; the modified wetting agent prepared by compounding with a defoaming agent, an antibacterial agent and an antistatic agent has good reproducibility, adhesion and film-forming properties.

[0024] 3. The present invention uses 4-vinyl-2,6-dimethoxy-phenol to modify it with 1,1,3,5,5-pentamethyl-3-phenyltrisiloxane, then compound it with phenol, and react it with formaldehyde to obtain a phenolic resin modified glue. 4-vinyl-2,6-dimethoxy-phenol has methoxy and butoxymethyl groups, which can enhance the thermal stability of the phenolic resin. The phenolic resin is first modified with silane and then synthesized so that the silicon element can be more evenly dispersed in the phenolic resin, so that the phenolic resin modified glue has excellent wear resistance and weather resistance.

[0025] 4. The flame retardant and antioxidant filler obtained by compounding the aminated boron nitride obtained by ball milling boron nitride and urea with alumina ceramic powder and carbon black powder can react and combine with the hydroxyl or aldehyde group of the phenolic resin modified glue through the amino group, thereby enhancing the interfacial bonding force between the flame retardant and antioxidant filler and the phenolic resin modified glue, and making the product have better wear resistance and antioxidant properties. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1: The composite high temperature resistant material containing glass fiber yarn of this example comprises the following raw materials in parts by mass: 100 parts of glass fiber cloth, 25 parts of modified sizing agent, 30 parts of phenolic resin modified glue, 3 parts of urotropine curing agent and 6 parts of flame retardant and antioxidant filler; The glass fiber cloth is made of glass fiber yarn through plain weaving, and the glass fiber yarn includes the following raw materials by mass: 64 parts of silicon dioxide, 16 parts of aluminum oxide, 6 parts of boron oxide, 7 parts of magnesium oxide and 7 parts of calcium carbonate; The modified impregnating agent comprises the following raw materials by mass: 20 parts of modified film-forming agent, 0.5 parts of antibacterial agent, 0.5 parts of antistatic agent, 0.5 parts of defoaming agent and 7 parts of lubricating solvent; The antibacterial agent is dibutyltin maleate; the antistatic agent is antistatic agent 1631; and the defoaming agent is DF-696.

[0028] The method for preparing the composite high temperature resistant material containing glass fiber yarn of this embodiment comprises the following steps: S1. Put silicon dioxide, aluminum oxide, boric acid, magnesium oxide and calcium carbonate into a mixer according to mass and stir for 30 minutes to obtain a glass mixture. Preheat the crucible to 1300°C, add the glass mixture several times, with an interval of 20 minutes between additions. After the additions are completed, heat the temperature to 1550°C and keep it warm for 6 hours. After the bubbles are discharged from the molten glass solution, the glass solution is made to flow out in the form of filaments through a porous plate. Apply a modified impregnation agent to the filamentary glass fiber through an oiling roller, and use a wire drawing wheel to draw the fiber at a drawing rate of 50m / min to obtain glass fiber filaments. The average diameter of the glass fiber filaments is 7.5μm. S2. According to the mass fraction, the glass fiber yarn is passed through a warping machine to remove impurities and wind the fiberglass yarn to form a glass fiber yarn, and the glass fiber yarn is used as warp and weft yarn, and is woven through a loom to form a cloth with a mesh count of 6 and a gram weight of 211 g / m 2 Fiberglass cloth; S3. After adding urotropine curing agent to the phenolic resin modified adhesive according to parts by mass, the glass fiber cloth is impregnated, and the flame retardant and antioxidant filler is bonded to both sides of the glass cloth, and the reaction is cured at 170° C. for 1 hour to obtain a crude composite flame retardant and antioxidant filler; S4. Cutting the crude composite flame retardant and antioxidant filler into required specifications to obtain a composite high temperature resistant material product containing glass fiber yarn.

[0029] The preparation method of the modified sizing agent of this embodiment comprises the following steps: S11. According to the mass parts, 20 parts of castor oil and 5.8 parts of methanol were added to a reactor, the temperature was raised to 70°C under stirring, 0.4 parts of an alkali catalyst was added, and after reacting for 2 hours, 5 wt% of dilute sulfuric acid was added until the pH of the reaction system was 3, and the reaction was allowed to stand for 24 hours to separate the layers, the upper layer of liquid was taken, washed with water until neutral, and castor oil methyl ester was obtained by low-pressure fractionation and impurity removal, and 20 parts of castor oil methyl ester and 3 parts of dibutyl ester were blended to obtain a lubricating solvent; S12, according to mass parts, add 10 parts of starch with a linear content of 60% to 80 parts of deionized water, stir at a low speed and then drop 6 parts of phenylsuccinic anhydride acetone solution, and adjust the pH to 8.5 with 10wt% sodium hydroxide solution, and add all the drops within 2 hours, react at 35°C for 3 hours, then drop 5wt% of dilute sulfuric acid to a pH of 7, filter and wash with deionized water and anhydrous ethanol in turn, dry at 40°C, and crush and sieve to obtain a modified film-forming agent; S13. Add 20 parts of modified film-forming agent, 0.5 parts of defoaming agent, 0.5 parts of antibacterial agent and 0.5 parts of antistatic agent to 7 parts of lubricating solvent according to mass parts, heat to 95°C under stirring and gelatinize for 1 hour to obtain a modified impregnating agent.

[0030] The preparation method of the phenolic resin modified adhesive of this embodiment comprises the following steps: S21, according to the mass parts, add 15 parts of 4-vinyl-2,6-dimethoxy-phenol into the reaction kettle, heat it to 55°C, dropwise add 2 parts of Custer platinum catalyst and 13.5 parts of 1,1,3,5,5-pentamethyl-3-phenyltrisiloxane, heat it to 85°C and react for 2h to obtain silane-modified 4-vinyl-2,6-dimethoxy-phenol; S22, according to the mass parts, add 115 parts of phenol and 15 parts of silane-modified 4-vinyl-2,6-dimethoxy-phenol into the reaction kettle, heat it to 55°C, add 1 part of magnesium tartrate and 70 parts of 37wt% formaldehyde solution after the phenol is completely melted, react at 105°C for 4h, and obtain a crude phenolic resin; S23, washing the crude phenolic resin with deionized water, distilling under reduced pressure, adding 80 parts of ethanol to dilute to obtain a phenolic resin modified glue.

[0031] The preparation method of the flame retardant and antioxidant filler of this embodiment comprises the following steps: S31, according to the mass parts, 6 parts of boron nitride, 150 parts of urea and 70 parts of deionized water were mixed evenly, added into a ball mill, and ball milled for 16 hours, then added into 200 parts of deionized water, ultrasonicated for 30 minutes, and filtered to collect the solid to obtain aminated boron nitride; S32. According to parts by mass, 5 parts of amidated boron nitride, 6 parts of alumina ceramic powder and 20 parts of carbon black powder are uniformly mixed to obtain a flame retardant and antioxidant filler.

[0032] Example 2: The composite high temperature resistant material containing glass fiber yarn of this example comprises the following raw materials in parts by mass: 100 parts of glass fiber cloth, 30 parts of modified sizing agent, 30 parts of phenolic resin modified glue, 3 parts of urotropine curing agent and 5 parts of flame retardant and antioxidant filler; The glass fiber cloth is made of glass fiber yarn through plain weaving, and the glass fiber yarn includes the following raw materials by mass: 65 parts of silicon dioxide, 17 parts of aluminum oxide, 6 parts of boron oxide, 5.7 parts of magnesium oxide and 6.3 parts of calcium carbonate; The modified impregnating agent comprises the following raw materials by mass: 20 parts of modified film-forming agent, 0.5 parts of antibacterial agent, 0.5 parts of antistatic agent, 0.5 parts of defoaming agent and 7 parts of lubricating solvent; The antibacterial agent is tributyltin oxide; the antistatic agent is alkyl dicarboxymethyl ammonium betaine; and the defoaming agent is AC-10.

[0033] The method for preparing the composite high temperature resistant material containing glass fiber yarn of this embodiment comprises the following steps: S1. Put silicon dioxide, aluminum oxide, boric acid, magnesium oxide and calcium carbonate into a mixer and stir for 35 minutes according to mass to obtain a glass mixture. Preheat the crucible to 1210°C, add the glass mixture several times, and add it at an interval of 25 minutes. After the addition is completed, heat it to 1570°C and keep it warm for 4 hours. After the bubbles are discharged from the molten glass solution, the glass solution is made to flow out in the form of filaments through a porous plate. Apply a modified impregnation agent to the filamentary glass fiber through an oiling roller, and use a wire drawing wheel to draw the fiber at a drawing rate of 40m / min to obtain glass fiber filaments. The average diameter of the glass fiber filaments is 13.1μm. S2. According to the mass fraction, the glass fiber yarn is passed through a warping machine to remove impurities and wind the fiber to make glass fiber yarn, and the glass fiber yarn is used as warp and weft yarn, and is woven through a loom to have a mesh count of 6 and a gram weight of 216g / m 2 Fiberglass cloth; S3, adding urotropine curing agent to the phenolic resin modified adhesive according to parts by mass, and then impregnating the glass fiber cloth, bonding the flame retardant and antioxidant filler on both sides of the glass cloth, and curing to obtain a crude composite flame retardant and antioxidant filler; S4. Cutting the crude composite flame retardant and antioxidant filler into required specifications to obtain a composite high temperature resistant material product containing glass fiber yarn.

[0034] The preparation method of the modified wetting agent and the flame retardant and antioxidant filler of this embodiment is the same as the preparation method of embodiment 1.

[0035] The phenolic resin modified adhesive of this embodiment is different from that of Embodiment 1 in that, in parts by mass, the parts of phenol, silane-modified 4-vinyl-2,6-dimethoxy-phenol and 37wt% formaldehyde solution are replaced by 100 parts of phenol, 10 parts of silane-modified 4-vinyl-2,6-dimethoxy-phenol and 65 parts of 37wt% formaldehyde solution.

[0036] Example 3, the composite high temperature resistant material containing glass fiber yarn of this example includes the following raw materials by mass: 80 parts of glass fiber cloth, 20 parts of modified sizing agent, 30 parts of phenolic resin modified glue, 1 part of urotropine curing agent and 5 parts of flame retardant antioxidant filler; The glass fiber cloth is made of glass fiber yarn through plain weaving, and the glass fiber yarn includes the following raw materials by mass: 65 parts of silicon dioxide, 17 parts of aluminum oxide, 6 parts of boron oxide, 5.7 parts of magnesium oxide and 6.3 parts of calcium carbonate; The modified impregnating agent comprises the following raw materials by mass: 20 parts of modified film-forming agent, 0.8 parts of antibacterial agent, 1 part of antistatic agent, 0.5 parts of defoaming agent and 7 parts of lubricating solvent; The antibacterial agent is dioctyltin dilaurate; the antistatic agent is alkyl dicarboxymethyl ammonium betaine; and the defoaming agent is DF-420.

[0037] The method for preparing the composite high temperature resistant material containing glass fiber yarn of this embodiment comprises the following steps: S1. Put silicon dioxide, aluminum oxide, boric acid, magnesium oxide and calcium carbonate into a mixer and stir for 50 minutes according to mass to obtain a glass mixture. Preheat the crucible to 1240°C, add the glass mixture several times, with an interval of 40 minutes between additions. After the additions are completed, heat the mixture to 1510°C and keep it warm for 8 hours. After the bubbles are discharged from the molten glass solution, the glass solution is made to flow out in the form of filaments through a porous plate. Apply a modified impregnation agent to the filamentary glass fiber through an oiling roller, and use a wire drawing wheel to draw the fiber at a drawing rate of 50m / min to obtain glass fiber filaments. The average diameter of the glass fiber filaments is 6.5μm. S2. According to the mass fraction, the glass fiber yarn is passed through a warping machine to remove impurities and wind the fiber to make glass fiber yarn, and the glass fiber yarn is used as warp and weft yarn, and is woven through a loom to have a mesh count of 7 and a gram weight of 217g / m 2 Fiberglass cloth; S3. After adding urotropine curing agent to the phenolic resin modified adhesive according to parts by mass, the glass fiber cloth is impregnated, and the flame retardant and antioxidant filler is bonded to both sides of the glass cloth, and the reaction is cured at 170° C. for 1 hour to obtain a crude composite flame retardant and antioxidant filler; S4. Cutting the crude composite flame retardant and antioxidant filler into required specifications to obtain a composite high temperature resistant material product containing glass fiber yarn.

[0038] The preparation method of the phenolic resin modified adhesive and the flame retardant and antioxidant filler of this embodiment is the same as the preparation method of Example 1.

[0039] The modified wetting agent of this embodiment is different from that of Embodiment 1 in that, by weight, the starch with a linear chain content of 60% is replaced by 15 parts of starch with a linear chain content of 55%.

[0040] Example 4: The composite high temperature resistant material containing glass fiber yarn of this example comprises the following raw materials in parts by mass: 100 parts of glass fiber cloth, 25 parts of modified sizing agent, 30 parts of phenolic resin modified glue, 3 parts of urotropine curing agent and 6 parts of flame retardant and antioxidant filler; The glass fiber cloth is made of glass fiber yarn through plain weaving, and the glass fiber yarn includes the following raw materials by mass: 65 parts of silicon dioxide, 17 parts of aluminum oxide, 6 parts of boron oxide, 5.7 parts of magnesium oxide and 6.3 parts of calcium carbonate; The modified impregnating agent comprises the following raw materials by mass: 25 parts of modified film-forming agent, 1 part of antibacterial agent, 1 part of antistatic agent, 1 part of defoaming agent and 10 parts of lubricating solvent; The antibacterial agent is dibutyltin maleate; the antistatic agent is stearyl trimethyl quaternary ammonium salt; and the defoaming agent is DF-420.

[0041] The method for preparing the composite high temperature resistant material containing glass fiber yarn of this embodiment comprises the following steps: S1. Put silicon dioxide, aluminum oxide, boric acid, magnesium oxide and calcium carbonate into a mixer and stir for 30 minutes according to mass to obtain a glass mixture. Preheat the crucible to 1210°C, add the glass mixture several times, and add it at an interval of 20 minutes. After the addition is completed, heat it to 1590°C and keep it warm for 4 hours. After the bubbles are discharged from the molten glass solution, the glass solution is made to flow out in the form of filaments through a porous plate. Apply a modified impregnation agent to the filamentary glass fiber through an oiling roller, and use a wire drawing wheel to draw the fiber at a drawing rate of 45m / min to obtain glass fiber filaments. The average diameter of the glass fiber filaments is 6.2μm. S2. According to the mass fraction, the glass fiber yarn is passed through a warping machine to remove impurities and wind the fiber to make glass fiber yarn, and the glass fiber yarn is used as warp and weft yarn, and is woven through a loom to have a mesh count of 7 and a gram weight of 214g / m 2 Fiberglass cloth; S3. After adding urotropine curing agent to the phenolic resin modified adhesive according to parts by mass, the glass fiber cloth is impregnated, the flame retardant and antioxidant filler is bonded to both sides of the glass cloth, and the reaction is cured at 150° C. for 2 hours to obtain a crude composite flame retardant and antioxidant filler; S4. Cutting the crude composite flame retardant and antioxidant filler into required specifications to obtain a composite high temperature resistant material product containing glass fiber yarn.

[0042] The preparation method of the modified sizing agent and the phenolic resin modified adhesive of this embodiment is the same as the preparation method of embodiment 1.

[0043] The flame retardant and antioxidant filler of this embodiment is different from that of Embodiment 1 in that, in parts by mass, the parts of boron nitride and urea are replaced by 5 parts of boron nitride and 100 parts of urea.

[0044] Comparative Example 1: The difference between this comparative example and Example 1 is that the modified wetting agent is replaced by a paraffin-type wetting agent.

[0045] Comparative Example 2: This comparative example differs from Example 1 in that the amount of silane-modified 4-vinyl-2,6-dimethoxy-phenol is replaced with 50 parts by mass.

[0046] Comparative Example 3: This comparative example differs from Example 1 in that the aminated boron nitride of the flame retardant and antioxidant filler is replaced by boron nitride.

[0047] Performance Testing According to JC / T841-2007 "Alkali-resistant Glass Fiber Mesh", the radial rupture strength and latitudinal rupture strength of the composite high-temperature resistant materials prepared in each embodiment and comparative example were measured; the composite high-temperature resistant materials prepared in each embodiment and comparative example were placed in a resistance box, kept at 450°C for 1 hour for high-temperature treatment, and the appearance, radial rupture strength and latitudinal rupture strength of the composite high-temperature resistant materials after high-temperature treatment were measured. The test results are shown in Table 1: Table 1 Appearance, radial breaking strength and latitudinal breaking strength test

[0048] According to GB3960-83 "Plastic Sliding Friction and Wear Test Method", the wear rate of the composite high temperature resistant material prepared in each embodiment and comparative example was measured on a friction and wear tester. The test results are shown in Table 2: Table 2 Wear rate test

[0049] It can be seen from the data in the above table that the radial breaking strength of the composite high temperature resistant materials obtained in Examples 1 to 4 before high temperature treatment is between 2443 and 2478 N / 50 mm and the latitudinal breaking strength is between 2403 and 2441 N / 50 mm, indicating that the composite high temperature resistant materials containing glass fiber yarns obtained in the present invention have excellent mechanical properties; after high temperature treatment, there is no crack on the surface of the composite high temperature resistant materials obtained in Examples 1 to 4, and the radial breaking strength after high temperature treatment is between 2401 and 2433 N / 50 mm and the latitudinal breaking strength is between 2353 and 237 7N / 50mm, the glass fiber cloth prepared by using paraffin type impregnation agent in comparative example 1 produces hairiness during weaving, resulting in poor impregnation effect with phenolic resin modified glue, so there are cracks on the surface of the material after high temperature treatment, and the radial breaking strength and the weft breaking strength are much lower than the data of each embodiment, indicating that the composite high temperature resistant material prepared by the present invention has excellent high temperature resistance and antioxidant properties; the wear rate of the composite high temperature resistant material prepared by embodiments 1 to 4 is between 0.58% and 0.63%, indicating that the composite high temperature resistant material prepared by the present invention has excellent wear resistance.

[0050] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0051] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite high temperature resistant material comprising glass fiber yarn, characterized in that: The raw materials include, by mass: 80-100 parts of glass fiber cloth, 20-30 parts of modified sizing agent, 20-30 parts of phenolic resin modified adhesive, 1-3 parts of urotropine curing agent and 5-6 parts of flame retardant antioxidant filler; The glass fiber cloth is made of glass fiber yarn through plain weaving or twisting weaving. The glass fiber yarn includes the following raw materials by mass: 64-66 parts of silicon dioxide, 15-18 parts of aluminum oxide, 5-6 parts of boron oxide, 5-8 parts of magnesium oxide and 5-8 parts of calcium carbonate; The modified impregnating agent comprises the following raw materials in parts by mass: 20-25 parts of modified film-forming agent, 0.5-1 parts of antibacterial agent, 0.5-1 parts of antistatic agent, 0.5-1 parts of defoaming agent and 7-10 parts of lubricating solvent.

2. The composite high temperature resistant material containing glass fiber yarn according to claim 1, characterized in that: The antibacterial agent is one or more combinations of dibutyltin maleate, tributyltin oxide, and dioctyltin dilaurate; the antistatic agent is one or more combinations of alkyl dicarboxymethyl ammonium ethyl lactone, stearyl trimethyl quaternary ammonium salt, and antistatic agent 1631.

3. A method for preparing a composite high temperature resistant material comprising glass fiber yarn, characterized in that: The steps include: S1. Put silicon dioxide, aluminum oxide, boric acid, magnesium oxide and calcium carbonate into a mixer and stir for 30-50 minutes to obtain a glass mixture. Preheat the crucible to 1200-1300°C, add the glass mixture several times, with an interval of 20-40 minutes between additions. After the additions are completed, heat the mixture to 1500-1600°C and keep it warm for 4-8 hours. After the bubbles are discharged from the molten glass solution, the glass solution is made to flow out in the form of filaments through a porous plate. The filamentary glass fibers are coated with a modified impregnation agent through an oiling roller, and the fiberglass is drawn by a collecting wheel to obtain glass fiber filaments. S2, passing the glass fiber yarn through a warping machine to remove impurities and wind the wire to make glass fiber yarn, and using the glass fiber yarn as warp yarn and weft yarn to weave glass fiber cloth through a loom; S3, adding urotropine curing agent to the phenolic resin modified glue to soak the glass fiber cloth, bonding the flame retardant and antioxidant filler on both sides of the glass cloth, and curing to obtain a crude composite flame retardant and antioxidant filler; S4. Cutting the crude composite flame retardant and antioxidant filler into required specifications to obtain a composite high temperature resistant material product containing glass fiber yarn.

4. The method for preparing a composite high temperature resistant material comprising glass fiber yarn according to claim 3, characterized in that: The mass ratio of silicon dioxide to aluminum oxide in S1 is 3.8-4:1, the mass ratio of magnesium oxide to calcium carbonate is 0.9-1:1, the drawing speed of the wire drawing wheel is 40-50 m / min, and the average diameter of the glass fiber is 5-15 μm; the single yarn density of the warp and weft in S2 is 27-30 tex, the mesh number of the glass fiber is 6-7, and the gram weight is 200-220 g / m 2 ; The curing in S3 is carried out at 150-170° C. for 1-2 hours.

5. The method for preparing a composite high temperature resistant material containing glass fiber yarn according to claim 3, characterized in that: The method for preparing the modified wetting agent in S1 comprises the following steps: S11. Add 15-20 parts of castor oil and 4.1-5.8 parts of methanol to a reactor by weight, heat to 60-70°C under stirring, add 0.2-0.5 parts of an alkali catalyst, react for 1-2 hours, add 5wt% of dilute sulfuric acid until the pH of the reaction system is 2-3, let stand for 20-24 hours to separate the layers, take the upper layer of liquid, wash with water until neutral, remove impurities by low-pressure fractionation to obtain castor oil methyl ester, blend 15-20 parts of castor oil methyl ester and 1.5-3 parts of dibutyl ester to obtain a lubricating solvent; S12, according to mass parts, add 10-20 parts of starch with a linear content of 55-60% to 80-100 parts of deionized water, stir evenly at a low speed, then drop 6-12 parts of phenylsuccinic anhydride acetone solution, and adjust the pH to 8.4-8.6 with 10wt% sodium hydroxide solution, and drip it within 2-3 hours, react at 30-35°C for 2-3 hours, then drop 5wt% of dilute sulfuric acid to a pH of 6.5-7, filter and wash with deionized water and anhydrous ethanol in turn, dry at 30-40°C, and pulverize and sieve to obtain a modified film-forming agent; S13. Add 20-25 parts of modified film-forming agent, 0.5-1 parts of defoaming agent, 0.3-0.5 parts of antibacterial agent and 0.5-1 parts of antistatic agent to 7-10 parts of lubricating solvent in parts by mass, raise the temperature to 85-95°C under stirring and gelatinize for 1-2 hours to obtain a modified impregnating agent.

6. The method for preparing a composite high temperature resistant material comprising glass fiber yarn according to claim 5, characterized in that: The mass ratio of castor oil to methanol in the S11 is 10:2.7-2.

9.

7. The method for preparing a composite high temperature resistant material containing glass fiber yarn according to claim 3, characterized in that: The preparation method of the phenolic resin modified adhesive in S3 comprises the following steps: S21, according to the mass parts, add 10-15 parts of 4-vinyl-2,6-dimethoxy-phenol into the reaction kettle, heat it to 50-55°C, dropwise add 0.5-2 parts of catalyst and 8-14 parts of 1,1,3,5,5-pentamethyl-3-phenyltrisiloxane, heat it to 80-90°C and react for 2-3h to obtain silane-modified 4-vinyl-2,6-dimethoxy-phenol; S22, according to the mass parts, add 100-115 parts of phenol and 10-15 parts of silane-modified 4-vinyl-2,6-dimethoxy-phenol into the reaction kettle, heat it to 50-55° C., add 0.5-2 parts of metal salt catalyst and 60-70 parts of 37wt% formaldehyde solution after the phenol is completely melted, react at 100-110° C. for 4-8h, and obtain a crude phenolic resin; S23, washing the crude phenolic resin with deionized water, distilling under reduced pressure, adding 50-80 parts of ethanol to dilute to obtain a phenolic resin modified glue.

8. The method for preparing a composite high temperature resistant material containing glass fiber yarn according to claim 7, characterized in that: The catalyst in S21 is one or more combinations of platinum chloride, cyclooctadiene nickel, and Custer platinum catalyst, and the metal salt catalyst in S22 is one or more combinations of zinc acetate, magnesium tartrate, and tin oxalate.

9. The method for preparing a composite high temperature resistant material containing glass fiber yarn according to claim 3, characterized in that: The method for preparing the flame retardant and antioxidant filler in S3 comprises the following steps: S31, according to the mass parts, 5-6 parts of boron nitride, 100-150 parts of urea and 50-70 parts of deionized water were mixed evenly, added to a ball mill, and ball milled for 12-16 hours, then added to 200 parts of deionized water, ultrasonicated for 15-30 minutes, and filtered to collect the solid to obtain aminated boron nitride; S32. According to the mass parts, 4-5 parts of amino boron nitride, 5-6 parts of alumina ceramic powder and 20-30 parts of carbon black powder are uniformly mixed to obtain a flame retardant and antioxidant filler.

10. The method for preparing a composite high temperature resistant material containing glass fiber yarn according to claim 9, characterized in that: The average particle size of the alumina ceramic powder in S32 is 1-3 μm, and the average particle size of the carbon black powder is 10-30 μm.

Citation Information

Patent Citations

  • Preparation process of a high temperature and corrosion resistant electronic grade glass fiber cloth

    CN110863360B

  • Environment-friendly grinding wheel mesh and manufacturing method thereof

    CN117484407A

  • Application of organic silicon modifier in modified thermosetting phenolic resin

    CN102675572A

  • A method for preparing an esterified starch film former for glass fiber wetting

    CN103232548A

  • High-toughness glass fiber cloth and preparation method thereof

    CN115652500A